MicroRNA-10b inhibits proliferation, migration and invasion in cervical cancer cells via direct targeting of insulin-like growth factor-1 receptor - Hou, Ren (Oncol Lett, 2017)
MicroRNAs are deregulated in numerous types of human cancers and have crucial roles in the carcinogenesis and progression of human cancers. MicroRNA-10b (miR-10b) has been studied in several types of human cancer. However, the expression and roles of miR-10b in cervical cancer remain unknown. In the present study, the expression, functions and molecular mechanisms of miR-10b were explored in cervical cancer. The present data revealed that miR-10b was significantly downregulated in cervical cancer tissues and cell lines. In addition, miR-10b overexpression inhibited the proliferation, migration and invasion of cervical cancer cells, while miR-10b under-expression had the opposite effect. Based on bioinformatics analysis, a luciferase reporter assay and western blot analysis, insulin-like growth factor-1 receptor (IGF-1R) was identified as a direct target of miR-10b in cervical cancer. In addition, IGF-1R small interfering RNA-mediated knockdown of IGF-1R also inhibited the proliferation, migration and invasion of the cervical cancer cells. In conclusion, the present study demonstrated that miR-10b serves an important role in cervical cancer progression by targeting IGF-1R.